2005
DOI: 10.1161/circulationaha.104.526673
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate and Inappropriate Ventricular Therapies, Quality of Life, and Mortality Among Primary and Secondary Prevention Implantable Cardioverter Defibrillator Patients

Abstract: Background-Implantable cardioverter defibrillators (ICDs) reduce mortality in primary and secondary prevention.Quality of life, mortality, appropriate therapies for specific ventricular rhythms, and inappropriate therapies for supraventricular tachycardia (SVT) were compared among 582 patients (primary preventionϭ248; secondary preventionϭ334) in PainFREE Rx II, a 634-patient prospective, randomized study of antitachycardia pacing or shocks for fast ventricular tachycardia (FVT). Methods and Results-ICDs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(36 citation statements)
references
References 37 publications
(36 reference statements)
0
35
1
Order By: Relevance
“…22 In another clinical trial of 800 patients assigned to antiarrhythmic drugs vs. ICD groups, at 1-year follow-up, both groups had alterations in QOL related to adverse symptoms, and the ICD patients' sporadic shocks were associated with reduced QOL. 21 However, in 3 other long-term follow-up studies (n = 59, 22 n = 634, 19 and n = 35, 23 ) no significant difference in overall perceptions of QOL was evident. Conversely, in a study of implants after 1 to 6 years (n = 89), researchers reported significantly worse health changes in physical functioning, social functioning, and restricted roles because of physical problems.…”
Section: Quality Of Lifementioning
confidence: 90%
See 1 more Smart Citation
“…22 In another clinical trial of 800 patients assigned to antiarrhythmic drugs vs. ICD groups, at 1-year follow-up, both groups had alterations in QOL related to adverse symptoms, and the ICD patients' sporadic shocks were associated with reduced QOL. 21 However, in 3 other long-term follow-up studies (n = 59, 22 n = 634, 19 and n = 35, 23 ) no significant difference in overall perceptions of QOL was evident. Conversely, in a study of implants after 1 to 6 years (n = 89), researchers reported significantly worse health changes in physical functioning, social functioning, and restricted roles because of physical problems.…”
Section: Quality Of Lifementioning
confidence: 90%
“…Examples include Shortform 36, which was used in many ICD intervention trials, [18][19][20][21][22] the Ferrans and Powers Quality of Life Index (Cardiac Version), [22][23][24]25 QOL OVER TIME Research suggests that patients experience greater psychological distress during the early recovery periods 26 and when receiving device discharges. 27 At implant, factors such as age, gender, optimism, functional status, and history of sudden cardiac death influence mood disturbance.…”
Section: Quality Of Lifementioning
confidence: 99%
“…In addition to the ECG monitoring function, the ATP function is another method of managing VAs with this system. Numerous clinical studies have shown that the majority of VA events resulting from VT are terminated by ventricular pacing (11,12,18,19). In the present study, induced VAs were effectively terminated by ATP in the rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…An ICD with a remote monitoring function has been successfully used to effectively terminate VAs by anti-tachycardia pacing (ATP) and shocks, and manages alarm messages from patients (911). The PainFREE Rx and PainFREE Rx II trials showed that ATP terminates the majority of malignant ventricular tachycardias (VTs) (11,12). Animal models are helpful for testing the efficacy of novel drugs and the feasibility of using novel implantable electronic cardiovascular devices (IECDs) with telecommunications technologies for monitoring and terminating VAs.…”
Section: Introductionmentioning
confidence: 99%
“…The Pacing Fast Ventricular Tachycardia Reduces Shock Therapies (Pain-FREE Rx II) trial [32] showed that patients randomized to receive shock-only, 34% of fast VT episodes terminated spontaneously before therapy, suggesting that a considerable proportion of ATP intervention, which is delivered before a shock, may be unnecessary. Furthermore, ATP is not without risk; it is possible for ATP to accelerate VT to polymorphic VT or VF [33][34][35] which has been associated with a higher mortality risk [36]. In conclusion, the lack of ATP function in the S-ICD is a contentious one [37].…”
Section: Aha/acc/hrs Guideline For Management Of Patients With Ventrimentioning
confidence: 99%